2010
DOI: 10.1177/0957926509353847
|View full text |Cite
|
Sign up to set email alerts
|

Peer talk as a ‘double opportunity space’: The case of argumentative discourse

Abstract: We propose a theoretical view of peer talk as a ‘double opportunity space’, functioning concurrently on the plane of meaning making within childhood culture, as a locus for the co-construction of children’s social world and peer culture, while at the same time affording opportunities for the development of discursive learning (Blum-Kulka, 2005; Blum-Kulka et al., 2004: 308). In the present article, we provide further evidence for this twofold concept by analyzing peer talk in preschoolers’ genre of argumentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 67 publications
1
18
0
6
Order By: Relevance
“…Such resources are utilized, for example, as generators of childhood culture and the peer community (Hamo and Blum-Kulka, 2007;Kyratzis, 2004), allow for managing status within the peer group (Goodwin and Kyratzis, 2007), and offer children unique affordances for experiencing and developing a range of at Bobst Library, New York University on April 12, 2015 dcm.sagepub.com Downloaded from linguistic, discursive, and literate skills (Zadunaisky-Ehrlich and Blum-Kulka, 2010). However, despite their centrality in children's lives, media contents have not received focused attention as one of these resources (Cekaite et al, 2014).…”
Section: Child Peer Talk As a Double Opportunity Spacementioning
confidence: 99%
“…Such resources are utilized, for example, as generators of childhood culture and the peer community (Hamo and Blum-Kulka, 2007;Kyratzis, 2004), allow for managing status within the peer group (Goodwin and Kyratzis, 2007), and offer children unique affordances for experiencing and developing a range of at Bobst Library, New York University on April 12, 2015 dcm.sagepub.com Downloaded from linguistic, discursive, and literate skills (Zadunaisky-Ehrlich and Blum-Kulka, 2010). However, despite their centrality in children's lives, media contents have not received focused attention as one of these resources (Cekaite et al, 2014).…”
Section: Child Peer Talk As a Double Opportunity Spacementioning
confidence: 99%
“…One discourse valued in schools is the ability to build an argument. A definition of an argumentation event is when at least two parties take alternative positions on the same issue and develop their adversative positions by providing justifications, support, or explanations (Zadunaisky Ehrlich and Blum‐Kulka ). Key strategies in argument building include positioning oneself as knowledgeable on the topic (i.e., expert) and presenting evidence (e.g., accessing authorities) for a stance (Goshgarian and Krueger ).…”
Section: Discourse In Official Spacesmentioning
confidence: 99%
“…A third focus needs to include the ways peer talk relates to pragmatic language development (Blum‐Kulka and Snow ). Peer talk can be seen as a “double developmental space,” offering potential for both social and linguistic development (Zadunaisky Ehrlich and Blum‐Kulka :212). The symmetrical participation structure of peer groups is a critical site for exploring language development with the potential for collaboration, which allows for reciprocity in shifting between expert and novice roles in moment‐to‐moment interactions (Blum‐Kulka and Snow ).…”
Section: Oral Language Development With Peersmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have also found that knowledge of these dialogic interactions for argumentative purposes has its origins at an early age. Ehrlich and Blum-Kulka (2010) analyzed preschoolers' peer talk in natural interactions to demonstrate that very young students may employ narrative reports of playground events, examine word definitions, provide instructions on how to play a game, or discuss an issue from different perspectives to construct arguments, as when a narrative is employed to make a claim. An analysis of two preschoolers' arguments in trading and bargaining Pokémon stickers, for instance, revealed that refusal by one to give a sticker to the other resulted in the use of arguments involving appeals to third-party participants as well as addressing each other in the third person, strategies involving defining social relationships and ethos.…”
Section: The Use Of Student-teacher Reciprocal Dialogic Interactionsmentioning
confidence: 99%